алгебра 7 класс гдз

Номер 737

Условие:

Упростите выражение:
а) (1 - х + 4х2 - 8x3) + (2x3 + х2 - 6х - 3) - (5х3 + 8x2);
б) (0,5а - 0,6b + 5,5) - (-0,5а + 0,4b) + (1,3b - 4,5).

 

Ответ:

a) (1 - х + 4х2 - 8x3) + (2x3 + х2 - 6х - 3) - (5х3 + 8x2) = 1 - x + 4x2 - 8x3 + 2x3 + x2 - 6x - 3 - 5x3 - 8x2 =
= -11x3 - 3x2 - 7x - 2;
6) (0,5а - 0,6b + 5,5) - (-0,5а + 0,4b) + (1,3b - 4,5) = 0,5a - 0,6b + 5,5 + 0,5a - 0,4b + 1,3b - 4,5 = a + 0,3b + 1.

share with Whatsapp
share with Telegram
powered by social2s